Cotton Germination and Emergence under High Diurnal Temperatures - Raphael, Juan P. A. [UNESP]; Gazola, Bruno [UNESP]; Nunes, Jesion G. S. [UNESP]; Macedo, Gabrielle C. [UNESP]; Rosolem, Ciro A. [UNESP] (Crop Science Soc Amer, 2017)
In tropical climates, high soil temperatures during the cotton (Gossypium hirsutum L.) planting season impair seed germination and plant emergence, resulting in poor stand establishment. Under these conditions, the performance of cultivars presently in use is not known. The aim of this study was to evaluate germination and emergence of cotton cultivars under diurnal high temperature cycles without water restriction. Three experiments were conducted in germination chambers, testing six cotton cultivars and four diurnal cycles with maximum temperatures of 20, 30, 40, and 50 degrees C. The diurnal cycle with a maximum temperature of 30 degrees C resulted in the greatest germination and emergence rates. Under a maximum diurnal temperature of 40 degrees C, cultivars with higher seed weight were the least impaired, resulting in higher germination and emergence rates than cultivars with smaller seeds. There was a positive correlation between seed weight and seedling length (r = 0.57), as well as seedling dry weight (r = 0.56). The seeds of modern cultivars developed for tropical environments are tolerant to maximum daily temperatures up to 40 degrees C, which is higher than previously reported for older cultivars. However, seed exposure to a temperature of 50 degrees C for only 5.5 h is enough to impair the germination and prevent emergence. The correlation between seed weight and seedling dry weight is positive and greater as the temperature increases or decreases from 30 degrees C, showing that the initial seed weight is determinant for the final seedling dry weight under temperatures departing from the optimal.